Age-related immune response disparities between adults and children with severe COVID-19: a case–control study in China - Hongliang Chen; Hongliang Chen; Yuan Li; Liping Yuan; Fen Liu; Qian Sun; Qian Sun; Qingkai Luo; Yefei Lei; Yinglan Hou; Jiayan Li; Liang Cai; et al. (Frontiers in Microbiology)
BackgroundElucidation of immune response differences is critical for uncovering underlying mechanisms and developing potential intervention measures among adults and children with COVID-19.MethodsIn this retrospective study, we analyzed serum biochemical markers and cytokine profiles among adults and children with COVID-19 in the First People’s Hospital of Chenzhou in Hunan, China from 1 December 2022 to 13 February 2023. A case–control study was conducted using propensity score matching (PSM) to mitigate possible confounding factors.ResultsThe significant differences observed included lymphocyte exhaustion, an increased neutrophil-to-lymphocyte (NEU/LYM) ratio, high levels of C-reactive protein (CRP), and a cytokine storm, characterized by high levels of Th1 proinflammatory cytokines, including interleukin 1β (IL-1β), IL-6, IL-8, interferon type I (IFN-γ), and tumor necrosis factor (TNF-α) in the lung among severe adult COVID-19 patients. Additionally, systemic immune responses were observed in children with COVID-19.ConclusionSignificant differences in immune responses between adults and children with COVID-19 highlight the different mechanisms and potential intervention measures of COVID-19.